FKBP11 upregulation promotes proliferation and migration in hepatocellular carcinoma - Thokerunga, Erick; Huang, Fangfang; Bongolo, Christian Cedric; Rugera, Simon Peter; Akankwatsa, Gilbert; Tu, Jian-Cheng (Cancer Biomarkers, 2023)
Background: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer related deaths world over. Early\ diagnosis and effective treatment monitoring significantly improves patients’ outcomes. FKBP11 gene is highly expressed in HCC and could play a role in its development, early diagnosis and treatment. Objective: This study aimed to evaluate the expression of FKBP11 in HCC, its correlation with patients’ clinical characteristics and potential role in HCC development. Methods: Expression was determined by bioinformatics analysis, quantitative real-time PCR, western blot, and immunohistochemistry. CCK-8, Transwell and wound healing assays were used to investigate involvement in HCC development. Results: FKBP11 was significantly upregulated in HCC cells, tissues and blood (all p < 0.001). Its receiver operator characteristic (ROC) curve had an AUC of 0.864 (95% CI: 0.823–0.904), at a sensitivity of 0.86 and specificity of 0.78 indicating a good diagnostic potential in HCC. Its expression was markedly reduced after surgery (p < 0.0001), indicating a potential application in HCC treatment follow-up. Knockdown of FKBP11 in HCC cells attenuated proliferation and migration, suggesting a possible role in HCC pathogenesis. Conclusion: This study thus found that FKBP11 is upregulated in HCC, and the upregulation promotes HCC development. FKBP11 levels are significantly reduced post-surgery and could be a potential diagnostic and prognostic marker for HCC.
Keywords: FKBP11; Biomarker; Diagnosis; Hepatitis B virus; Hepatocellular carcinoma